3D printing of ceramics and graphene circuits-on-ceramics by thermal bubble inkjet technology and high temperature sintering. Issue 8 (1st June 2020) - Huang, Zheguan; Tang, Yang; Guo, Hao; Feng, Xiaoyuan; Zhang, Tingting; Li, Peng; Qian, Bo; Xie, Yonglin
Abstract: Alumina ceramics and graphene circuits-on-ceramics were 3D printed using inkjet technology. Water-based binders for ceramics and graphene oxide inks were prepared and jetted through thermal inkjet printhead. To increase the density of the 3D printed ceramics, two steps sintering and one step infiltration were performed. The sintering temperature dependent structure properties of the printed ceramics were systematically studied. The 3D printed α-Al2 O3 ceramic sintered at 1600 °C for 2 h has achieved maximum density of 95.2%, volume shrinkage rate of 32%, Vickers hardness of 291.6 Hv, surface roughness of 3.7 μm, and maximum compression strength and flexural strength of 89 MPa and 49.4 MPa, respectively. The average adhesion of reduced graphene oxide (rGO) to 3D printed α-Al2 O3 ceramic is 7.5 N/m. The printed graphene circuits-on-ceramics has achieved conductivity of 5.34 × 10 2 S m −1 after annealing at 600 °C in nitrogen atmosphere.